2021
DOI: 10.3390/pharmaceutics13030339
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin S Cleaves BAX as a Novel and Therapeutically Important Regulatory Mechanism for Apoptosis

Abstract: Certain lysosomal cathepsin proteins have come into focus as being good candidates for therapeutic targeting, based on them being over-expressed in a variety of cancers and based on their regulation of the apoptotic pathway. Here, we report novel findings that highlight the ability of cathepsin S expression to be up-regulated under Paclitaxel-stimulatory conditions in kidney cell lines and it being able to cleave the apoptotic p21 BAX protein in intact cells and in vitro. Consistent with this, we demonstrate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…Collectively, such findings highlight a novel approach for inhibitor design targeted at BAX stabilization as a foresight, for this regulatory axis of the intrinsic apoptotic pathway. As proof of principle, CS-PEP1 enhanced apoptotic cell numbers at low doses, in good agreement with its intended purpose [ 79 ]. Such findings do suggest that pro-apoptotic proteins (such as BAX), along with their upstream regulator proteases, can be simultaneously targeted by a single therapeutic that can serve a dual purpose.…”
Section: Pro-apoptotic Bax and Bak As Substrate Proteins For Cathepsin Proteasesmentioning
confidence: 65%
See 4 more Smart Citations
“…Collectively, such findings highlight a novel approach for inhibitor design targeted at BAX stabilization as a foresight, for this regulatory axis of the intrinsic apoptotic pathway. As proof of principle, CS-PEP1 enhanced apoptotic cell numbers at low doses, in good agreement with its intended purpose [ 79 ]. Such findings do suggest that pro-apoptotic proteins (such as BAX), along with their upstream regulator proteases, can be simultaneously targeted by a single therapeutic that can serve a dual purpose.…”
Section: Pro-apoptotic Bax and Bak As Substrate Proteins For Cathepsin Proteasesmentioning
confidence: 65%
“…While this could have been due to a number of reasons, from recent studies, our findings were supportive of BAX being directly cleaved to p18BAX in vitro by cathepsin S (at pH 5 or 7) and to complete digestion within intact mammalian cells. Moreover, the inhibition of cathepsin S had the effect of stabilizing p21BAX [ 79 ]. Based on the functional role of BAX and BAK up-regulating MOMP and apoptosis, many structural studies have revealed the potential to disrupt the interaction between the BAK BH3-domain with the hydrophobic groove of its cognate anti-apoptotic proteins, through designing BH3-mimetics and thus increasing the availability of monomeric BAK protein for MOMP and apoptosis induction [ 44 ].…”
Section: Pro-apoptotic Bax and Bak As Substrate Proteins For Cathepsin Proteasesmentioning
confidence: 99%
See 3 more Smart Citations